Essays on time allocation - Mills, Richard (2023)
This thesis contributes to important research questions on ‘time allocation’. We provide three largely independent but related chapters (Chapters I, II, and III), examining various ways people deviate from ‘optimal’ time allocation behaviour. We focus on literature at the intersection between how various forms of 'scarcity' affect judgement and decision-making as well as how individuals ‘bracket’ their choices.